The performance of maternal role at neonatal care unit - literature review - Elenice Valentim Carmona; Maria Helena Baena de Moraes Lopes; Antonieta Keiko Kakuda Shimo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
To assume maternal role might not be an easy experience in the neonatal care unit due to the special characteristics of the situation and the environment and because of the mother's fragility, being distant from the child and without decision power. The aim of this study was to make a revision on the performance of maternal role in the hospitalization of the newborn at neonatal unit and to check which is the influence of nursing staff in this process. Method applied was through a data base (LILACS, MEDLINE) within a period of ten years (1993 - 2003). It was verified that the hospitalization of the newborn presents certain aspects that makes the performance of maternal role very difficult and it could be aggravated by the nursing assistance that ignores maternal needs.